UPAYA TANGGAP DARURAT KEBAKARAN DI INSTALASI GIZI SEBUAH RUMAH SAKIT SWASTA KOTA SEMARANG - Bernardus Oktavian Widyantara; Hanifa Maher Denny; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Hospital is a health service institutions for communities with their own characteristics that are influenced by the development of health scienc, technological progress and socio-economic life of the people who must able to continue to improve quality services and affordable by the community in order to realize the highest degree of health. Hospital buildings are buildings that have a high risk of fire. It is based on the results of identification found the main source of the cause of the fire. Such as the use of electrical equipments, short circuit of electric current, using pressurized gas cylinders, using various of liquid and solid chemicals that are flammable. The purpose of the research is to get deep information about fire emergency response efforts at the nutrition installation of a private hospital in Semarang city. This research is a descriptive study with a qualitative approach. 4 main informations and triangulation of 2 instruments people. In this study using in depth interview guidelines and observation sheets. Based on the Ministerial Regulation of Public Works on Technological Guidelines for Fire Protection Management in Urban Areas. Fire management system in general is appropriate. An active fire protection system and a means of saving lives in a private hospital in Semarang city especially in nutrition installation has not been fully fulfilled.